2019
DOI: 10.1140/epjd/e2019-90263-5
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of radiobiological response functions by energy loss fluctuations and complexities in chromosome aberration induction: deactivation theory for proton therapy from cells to tumor control

Abstract: We employ a multi-scale mechanistic approach built upon our recent phenomenological / computational methodologies (Ref. [42]) to investigate radiation induced cell toxicities and deactivation mechanisms as a function of linear energy transfer in hadron therapy. Our theoretical model consists of a system of Markov chains in microscopic and macroscopic spatio-temporal landscapes, i.e., stochastic birth-death processes of cells in millimeter-scale colonies that incorporates a coarsegrained driving force to accoun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…We now turn to present RBE of in-vitro clonogenic cell survival assay of H460 cell lines, a type of non-small cell lung cancer (NSCLC). The dependence of SF on dose and LET were measured experimentally in our group [30] and fitted by 3D global fitting method by the present authors [16][17][18][19]. Shown RBE calculated using variable l (red dots) and constant chord length equal to 5µm (black dots), as recommended by ICRU 36.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We now turn to present RBE of in-vitro clonogenic cell survival assay of H460 cell lines, a type of non-small cell lung cancer (NSCLC). The dependence of SF on dose and LET were measured experimentally in our group [30] and fitted by 3D global fitting method by the present authors [16][17][18][19]. Shown RBE calculated using variable l (red dots) and constant chord length equal to 5µm (black dots), as recommended by ICRU 36.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study [19], we demonstrated that the linear density of DNA DSBs, ∆ l , a fundamental biological response function in a radiation field, is a variable of linear density of the collisions. To this ends, we recall the following relation derived in our first principle multi-scale study [19]…”
Section: A Mathematical Formalismmentioning
confidence: 98%
“…The steps involving these algebra is cumbersome, but it is straightforward to show 11 P½nðtÞ ¼ 1 À SF eff ½nðtÞ ð Þ N 0 :…”
Section: Calculation Of Pmentioning
confidence: 99%
“…As discussed in Ref. 11, L fits a linear-quadratic type-relation in dose with a and b, polynomial functions of stochastic lineal energy, y, or its deterministic counterpart, LET, that is,…”
Section: Calculation Of Pmentioning
confidence: 99%
See 1 more Smart Citation